Comparing and contrasting risk factors for heart failure in patients with and without history of myocardial infarction: data from HOMAGE and the UK Biobank. (18th April 2022) - Rastogi, Tripti; Ho, Frederick K.; Rossignol, Patrick; Merkling, Thomas; Butler, Javed; Clark, Andrew; Collier, Timothy; Delles, Christian; Jukema, J Wouter; Heymans, Stephane; Latini, Roberto; Mebazaa, Alexandre; et al.
Abstract : Aims: Myocardial infarction (MI) is among the commonest attributable risk factors for heart failure (HF). We compared clinical characteristics associated with the progression to HF in patients with or without a history of MI in the HOMAGE cohort and validated our results in UK Biobank. Methods and results: During a follow‐up of 5.2 (3.5–5.9) years, 177 (2.4%) patients with prior MI and 370 (1.92%) patients without prior MI experienced HF onset in the HOMAGE cohort ( n  = 26 478, history of MI: n  = 7241). Older age, male sex and higher heart rate were significant risk factors of HF onset in patients with and without prior MI. Lower renal function was more strongly associated with HF onset in patients with prior MI. Higher body mass index (BMI), systolic blood pressure and blood glucose were significantly associated with HF onset only in patients without prior MI (all p for interactions <0.05). In the UK Biobank ( n  = 500 001, history of MI: n  = 4555), higher BMI, glycated haemoglobin, diabetes and hypertension had a stronger association with HF onset in participants without prior MI compared to participants with MI (all p for interactions <0.05). Conclusion: The importance of clinical risk factors associated with HF onset is dependent on whether the patient has had a prior MI. Diabetes and hypertension are associated with new‐onset HF only in the absence of MI history. Patients may benefit from targeted risk management based on MI history. Abstract : Predictors of heart failure (HF) onset in patients with or without a history of myocardial infarction (MI). BMI, body mass index; CI, confidence interval; eGFR, estimated glomerular filtration rate; HbA1c, glycated haemoglobin; HR, hazard ratio; SBP, systolic blood pressure.